An international survey of healthcare providers’ knowledge of cardiac complications of cancer treatments - Peng, J.; Rushton, M.; Johnson, C.; Brezden-Masley, C.; Sulpher, J.; Chiu, Miliyun G; Graham, I. D; Dent, S. (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Cardio-oncology is a young sub-specialty that addresses the needs of cancer patients at risk of, or who have experienced cancer therapy related cardiac dysfunction (CTRCD). This study assessed clinicians’ understanding of cardio-oncology, opinions towards current practice, and approach to diagnosing and managing CTRCD. Methods A 45-question survey was administered online via Survey Monkey and WeChat to health care providers (HCPs) comprising of cardiologists, oncologists, and others from September 2017 to March 2018. Implementation of the survey followed a modified Dillman’s Total Design Method. Results In total, 160 responses were collected from 22 countries; majority were from cardiologists (53.8%) and oncologists (32.5%). The remaining 13.7% identified themselves as “others,” including general internists, cardio-oncologists, pediatric oncologists, radiation oncologists, cardiac rehabilitation therapists, nurse practitioners, research students, and pharmacists. In the setting of metastatic cancer, there was a difference in risk tolerance for cardiotoxicity between subspecialties. In this case, more cardiologists (36.7%) accepted a 5–10% risk of cardiotoxicity compared to oncologists (20.0%). Majority of cardiologists felt that cardiotoxicity should be monitored, even in asymptomatic cancer patients (55.8%). Only 12% of oncologists selected this response. In contrast, 50.0% of oncologists reported that cardiologists should be involved only when patients develop cardiotoxicity. In comparison, 6.5% of cardiologists selected this response. Majority of cardiologists stated that cardio-oncology clinics would significantly improve cancer patients’ prognosis (88.3%); only 45.8% of oncologists shared this opinion. Of all respondents, 66.9% stated they were familiar with a variety of international guidelines for managing cardiotoxicity. Of all oncologists, 65.3% indicated that they referred to these guidelines for clinical decision making. Conclusions Despite the growth of cardio-oncology clinics, there are significant knowledge gaps regarding prevention and treatment strategies for CTRCD among health care providers. Knowledge translation from guidelines and collaboration between cardiologists and oncologists are needed to improve cardiovascular outcomes of cancer patients.